2017
DOI: 10.1371/journal.pone.0172954
|View full text |Cite|
|
Sign up to set email alerts
|

Low magnitude high frequency vibration promotes adipogenic differentiation of bone marrow stem cells via P38 MAPK signal

Abstract: Low magnitude high frequency vibration (LMHFV) has been mainly reported for its influence on the musculoskeletal system, particularly the bone tissue. In the bone structure, osteogenic activity is the main focus of study with regards to LMHFV. However, adipogenesis, another important mode of differentiation in the bone marrow cavity that might be affected by LMHFV, is much less researched. Furthermore, the molecular mechanism of how LMHFV influences adipogenesis still needs to be understood. Here, we tested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…While most studies show proosteoblastic and antiadipocytic differentiation effects on MSCs [ 96 , 97 ], some contrary findings are reported. You’s group and Yu’s group found that LMHF vibration inhibited osteoblastic differentiation but promoted adipogenic differentiation of rat BM-MSCs [ 98 , 99 ]. You’s group reported that LMHF (0.3 g, 60 Hz, 1 h/1 day) vibration decreased osterix expression and inhibited mineralization in MSCs [ 98 ], while Yu’s group found that LMHF (0.3 g, 40 Hz, 15 min/day) vibration significantly increased the expression of PPARγ, C/EBPα , adiponectin , and the oil droplets [ 99 ].…”
Section: The Molecular Mechanisms Regulating Osteoblast and Adipocmentioning
confidence: 99%
See 1 more Smart Citation
“…While most studies show proosteoblastic and antiadipocytic differentiation effects on MSCs [ 96 , 97 ], some contrary findings are reported. You’s group and Yu’s group found that LMHF vibration inhibited osteoblastic differentiation but promoted adipogenic differentiation of rat BM-MSCs [ 98 , 99 ]. You’s group reported that LMHF (0.3 g, 60 Hz, 1 h/1 day) vibration decreased osterix expression and inhibited mineralization in MSCs [ 98 ], while Yu’s group found that LMHF (0.3 g, 40 Hz, 15 min/day) vibration significantly increased the expression of PPARγ, C/EBPα , adiponectin , and the oil droplets [ 99 ].…”
Section: The Molecular Mechanisms Regulating Osteoblast and Adipocmentioning
confidence: 99%
“…You’s group and Yu’s group found that LMHF vibration inhibited osteoblastic differentiation but promoted adipogenic differentiation of rat BM-MSCs [ 98 , 99 ]. You’s group reported that LMHF (0.3 g, 60 Hz, 1 h/1 day) vibration decreased osterix expression and inhibited mineralization in MSCs [ 98 ], while Yu’s group found that LMHF (0.3 g, 40 Hz, 15 min/day) vibration significantly increased the expression of PPARγ, C/EBPα , adiponectin , and the oil droplets [ 99 ]. Yu’s study also demonstrated that LMHF vibration promoted adipogenic differentiation of MSCs through activating p38 MAPK signaling.…”
Section: The Molecular Mechanisms Regulating Osteoblast and Adipocmentioning
confidence: 99%
“…Additionally, LIPUS directly acts on mesenchymal stem cells, osteoblasts, chondrocytes, or osteoclasts and affects their proliferation or differentiation [17]. In several studies published recently, vibration acceleration has been reported to promote osteogenic or adipogenic differentiation from bone marrow stromal cells [47][48][49]. Furthermore, Marycz et al reported that vibration acceleration under the conditions of 0.3 G, 35 Hz, for 15 minutes per day enhanced the chondrogenic differentiation of human adipose-derived mesenchymal stromal stem cells [50].…”
Section: Plos Onementioning
confidence: 99%
“…The mechanical HF vibration has been applied to cell cultures with the aim to mimic the mechanical environment of cells in vivo [9][10][11][12][13][14][15][16]. The mechanical impact effects on cells, to our best knowledge, have not yet been tested, despite that they could potentially be more in vivo like for many cell types.…”
Section: Introductionmentioning
confidence: 99%
“…In the stimulation the cell culture is often moved either in parallel (i.e. vertical HF vibration) [9,11,[13][14][15]17] or perpendicularly (i.e. horizontal HF vibration) [10,12,18] to the direction of gravity.…”
Section: Introductionmentioning
confidence: 99%